2022
DOI: 10.3390/met12111935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flow Behaviors at High Temperature of Two Press Hardening Boron Steels with Different Hardenability

Abstract: The deformation behavior and the constitutive description of materials are important in the design and numerical simulation of manufacturing processes. In this work, the rheological behavior of two quenchable boron steels was derived in the range of interest for the Press Hardening (PH) process. For this study, the following steps were performed: (i) Design of the specimen geometry adopted during the hot tensile tests in the Gleeble®3180 physical simulator. (ii) Performance of hot tensile tests at temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The specimens adopted during the physical simulation tests were tapered in the central section to reproduce the stamping and quenching phases in the die characterized by a high cooling rate. Palmieri et al [ 27–29 ] demonstrated that the reduction in the width and length of the central specimen zone leads to an increase in the cooling rate.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens adopted during the physical simulation tests were tapered in the central section to reproduce the stamping and quenching phases in the die characterized by a high cooling rate. Palmieri et al [ 27–29 ] demonstrated that the reduction in the width and length of the central specimen zone leads to an increase in the cooling rate.…”
Section: Methodsmentioning
confidence: 99%
“…This geometry, combined with compressed air released from nozzles present in the Gleeble system test chamber, ensured the replication of the quenching phase characterized by a cooling rate of about 10 2 K s À1 . [23,39] Figure 7a highlights that three K-type thermocouples were welded onto the face specimen, one of them was welded in the specimen center and the other two at about 5 and 15 mm from the center. The Gleeble physical simulator adopted for these tests heats the specimens by exploiting the Joule effect and it was equipped with a proportional-integralderivative (PID) controller that compared the temperature measured by the central thermocouple (pilot thermocouple) with the desired temperature and adjusted the current density accordingly.…”
Section: Lab-scale Experimentsmentioning
confidence: 99%
“…At 200 °C tempering, because of the carbon atoms image dislocation segregation and eliminating part of the internal stress, so the plasticity gradually increased. The slatted martensite got good toughness, mainly due to the presence of participating austenite between the slats, although its amount is small, its role cannot be ignored [18].…”
Section: Tensile Testmentioning
confidence: 99%